Clinical presentation and visual status of retinitis pigmentosa patients: a multicenter study in southwestern Nigeria - Onakpoya OH (Dove Medical Press, 2016)
Oluwatoyin Helen Onakpoya,1 Caroline Olufunlayo Adeoti,2 Tunji Sunday Oluleye,3 Iyiade Adeseye Ajayi,4 Timothy Majengbasan,4,5 Olayemi Kolawole Olorundare1 1Department of Ophthalmology, Obafemi Awolowo University Teaching Hospital, Ile-Ife, 2Department of Ophthalmology, Ladoke Akintola University of Technology Teaching Hospital, Osogbo, 3Department of Ophthalmology, University College Hospital, Ibadan, 4Department of Ophthalmology, University Teaching Hospital, Ado-Ekiti, 5Department of Ophthalmology, Federal Medical Centre, Ido-Ekiti, Nigeria Background: To review the visual status and clinical presentation of patients with retinitis pigmentosa (RP).Methodology: Multicenter, retrospective, and analytical review was conducted of the visual status and clinical characteristics of patients with RP at first presentation from January 2007 to December 2011. Main outcome measure was the World Health Organization’s visual status classification in relation to sex and age at presentation. Data analysis by SPSS (version 15) and statistical significance was assumed at P<0.05.Results: One hundred and ninety-two eyes of 96 patients with mean age of 39.08±18.5 years and mode of 25 years constituted the study population; 55 (57.3%) were males and 41 (42.7%) females. Loss of vision 67 (69.8%) and night blindness 56 (58.3%) were the leading symptoms. Twenty-one (21.9%) patients had a positive family history, with RP present in their siblings 15 (71.4%), grandparents 11 (52.3%), and parents 4 (19.4%). Forty (41.7%) were blind at presentation and 23 (24%) were visually impaired. Blindness in six (15%) patients was secondary to glaucoma. Retinal vascular narrowing and retinal pigmentary changes of varying severity were present in all patients. Thirty-five (36.5%) had maculopathy, 36 (37.5%) refractive error, 19 (20%) lenticular opacities, and eleven (11.5%) had glaucoma. RP was typical in 85 patients (88.5%). Older patients had higher rates of blindness at presentation (P=0.005); blindness and visual impairment rate at presentation were higher in males than females (P=0.029).Conclusion: Clinical presentation with advanced diseases, higher blindness rate in older patients, sex-related difference in blindness/visual impairment rates, as well as high glaucoma blindness in RP patients requires urgent attention in southwestern Nigeria. Keywords: retinitis pigmentosa, blindness, glaucoma, visual impairment, Nigeria